Manuskrip Mushaf Al-Qur`an Kertas Kuno (MMKK-A) Koleksi Museum Jenang dan Gusjigang Kudus Jawa Tengah: Kajian Kodikologi dan Rasm Berkaidah Hamzah - Vina Tsuroyya Najihah; Abdul Wadud Kasful Humam (Universitas Darussalam Gontor, 2025)
This study examines the Manuscript of Mushaf al-Qur`an Ancient Paper A (MMKK-A) a collection of the Jenang and Gusjigang Museum in Kudus. The purpose of this study is to describe the physical form of the manuscript through codicological studies and its textual content through analysing it on the basis of the code of writing hamzah formulated by Abū Amr al-Dāni dan Abū Dawūd Sulaimān al-Najāh known as shaikhāni fī al-rasm. The physical form of the manuscript through codicological studies and its textual content through analysing it on the basis of the code of writing hamzah formulated by Abū Amr al-Dāni dan Abū Dawūd Sulaimān al-Najāh known as shaikhāni fī al-rasm. The results of this study reveal that the Manuscript of Mushaf al-Qur`an Ancient Paper A (MMKK-A) was written around the 18th-19th centuries AD using European paper with a writing model in the form of khat naskhi. This manuscript consists of 30 Juz bound using thread, with a size of 33 cm long x 22.5 cm wide. As for the text analysis, the analysis of the rasm with hamzah rules is generally in accordance (ittīfaq) with the rules formulated by shaikhān fī al-rasm, and some words violate the formulation of one of them (ikhtilaf baina aḥaḍihima).